2018
DOI: 10.1007/s40843-018-9380-8
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed amorphous gallium-tin oxide thin film for low-voltage, high-performance transistors

Abstract: Gallium-tin oxide (GTO) semiconductor thin films were prepared by spin-coating with 2-methoxyethanol as the solvent. Their crystal structures, optical transparency, chemical states and surface morphologies, along with the electrical properties, were dependent on Ga contents and annealing temperatures. The optimized GTO channel layer was applied in the high-k Al 2 O 3 thin film transistor (TFT) with a low operation voltage of 2 V, a maximum field-effect mobility of 69 cm 2 V −1 s −1 , a subthreshold swing (SS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 54 publications
0
8
2
Order By: Relevance
“…According to Salameh et al [ 23 ], the E g of SnO 2 decreased from 3.97 to 3.53 eV after Zn loading but increased to 4.45 eV after co-doping with F. Han et al were also able to reduce the energy gap of sol-gel-prepared SnO 2 films from 3.8 to 3.1 eV by using Ti alloying and the oxygen vacancies created [ 32 ]. In contrast to our results, Ren et al [ 8 ] found that the E g of SnO 2 was 3.87 eV and was not changed even after doping with 10–50% Ga. Additionally, Ni doping was found to increase the E g of the spray-deposited SnO 2 films from 4.03 to 4.09 eV [ 17 ]. Guo et al obtained SnO 2 electrode with an energy gap of 1.74 V after (Ni, S)-co-doping [ 33 ].…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…According to Salameh et al [ 23 ], the E g of SnO 2 decreased from 3.97 to 3.53 eV after Zn loading but increased to 4.45 eV after co-doping with F. Han et al were also able to reduce the energy gap of sol-gel-prepared SnO 2 films from 3.8 to 3.1 eV by using Ti alloying and the oxygen vacancies created [ 32 ]. In contrast to our results, Ren et al [ 8 ] found that the E g of SnO 2 was 3.87 eV and was not changed even after doping with 10–50% Ga. Additionally, Ni doping was found to increase the E g of the spray-deposited SnO 2 films from 4.03 to 4.09 eV [ 17 ]. Guo et al obtained SnO 2 electrode with an energy gap of 1.74 V after (Ni, S)-co-doping [ 33 ].…”
Section: Resultscontrasting
confidence: 99%
“…created [32]. In contrast to our results, Ren et al [8] found that the Eg of SnO2 was 3.87 eV and was not changed even after doping with 10-50% Ga. Additionally, Ni doping was found to increase the Eg of the spray-deposited SnO2 films from 4.03 to 4.09 eV [17]. Guo et al obtained SnO2 electrode with an energy gap of 1.74 V after (Ni, S)-co-doping [33].…”
Section: Ftir and Uv-vis Spectroscopycontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike crystals with periodic lattice structures, amorphous thin films possess long-range disordered structures [1][2][3][4]. They are very useful in various fields including optics, electronics and catalysis due to their fruitful kinds ranging from metals to insulators [5][6][7][8][9][10][11]. Nevertheless, it is difficult to widely tune their properties via the amorphous structural manipulation [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%